INTERNATIONAL CONFERENCE ON EDUCATION, SCIENCE TECHNOLOGY AND HEALTH - Yuli Amalia; Ahmad Nasriadi; Akmalia Khairunnisa (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Students experience difficulties in working on and solving non-routine problems. This means that students' high-level thinking abilities are still relatively low. One solution isto use HOTS-based LKPD through the problem[1]based learning model. The aim of this research is to find out whether HOTS[1]based LKPD through the PBL model is effective in reducing absolute value inequality. This research is a type of quantitative research. The method used in this research is quasi-experimental design in the form of a nonequivalent control group design. The sample in this study was determined using the purposeful sampling technique. The experimental class was given treatment using HOTS-based LKPD via the PBL model, while the control class used a conventional learning model. The techniques and tools for collecting data for this research are through tests and documentation. The data analysis technique was tested through descriptive statistical analysis and inferential statistical analysis, as well as the N-Gain Score test. The results of this research show that learning using HOTS-based LKPD through the PBL model in the experimental class is within the effective criteria with a percentage level of effectiveness of 81.21%, while learning using the conventional model in the control class is within the criteria of being quite effective with a percentage level of effectiveness of 54.47 percent. The conclusion is that the HOTS-based LKPD through the PBL model is effective in reducing absolute value inequality material.